2014
DOI: 10.2298/abs1401099h
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and genotypes of macrolide-resistant Streptococcus pneumoniae in Serbia

Abstract: Although macrolides are widely used for treating pneumococcal infections, an increase in macrolide resistance might compromise their use. The objective of this study was to determine the prevalence of macrolide-resistant phenotypes and genotypes in macrolide-resistant S. pneumoniae isolates in Serbia. A total of 228 macrolide-resistant strains isolated during the period of 2009-2012, were analyzed. Macrolide resistance phenotypes were determined by a double disk diffusion test. The presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
2
1
1
Order By: Relevance
“…In our region, cMLSb phenotype was the most prevalent (38.2%) of all S. pneumoniae isolates from outpatient samples, whereas the M/MSb (33.3%) was dominant among hospital-acquired isolates. Different from our findings, authors from the Nišava district and central and northern parts of Serbia found that the dominant MLS resistance phenotype was cMLSb among hospital isolates of S. pneumoniae, but authors from Italy yielded results similar to our findings [22,23,25,26].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In our region, cMLSb phenotype was the most prevalent (38.2%) of all S. pneumoniae isolates from outpatient samples, whereas the M/MSb (33.3%) was dominant among hospital-acquired isolates. Different from our findings, authors from the Nišava district and central and northern parts of Serbia found that the dominant MLS resistance phenotype was cMLSb among hospital isolates of S. pneumoniae, but authors from Italy yielded results similar to our findings [22,23,25,26].…”
Section: Discussioncontrasting
confidence: 87%
“…In our region, we discovered a very high resistance rate to erythromycin in S. pneumoniae (63.6%, 35/55 community-and 77.8%, 7/9 hospital-acquired isolates), which was in accordance with findings by Dinić et al [22] (78.4% and 65.6%, respectively). However, Hadnađev et al [23] and Mijač et al [4] found lower rate of resistance to erythromycin in S. pneumoniae (36% and 45%, respectively) in their studies in Serbia. Some parts of Malta and Romania had similar prevalence rate of macrolide resistance among S. pneumoniae in 2012 and 2015 to our findings.…”
Section: Discussionmentioning
confidence: 88%
“…More than one third (36.4%) of pneumococcal isolates in Serbia in the 2009-2012 period expressed co-resistance to macrolides and penicillin. Multiresistant isolates were significantly more prevalent among children than adults [12].…”
Section: Discussionmentioning
confidence: 96%
“…Skoro četvrtina sojeva (~ 24%) bila je rezistentna na ≥ 3 antibiotika. Ovi rezultati su u skladu sa već objavljivanim podacima o rezistenciji S. pneumoniae na antibiotike u našoj zemlji, prema kojima su stope rezistencije tokom prve decenije 21. veka iznosile ~ 36% na penicilin i ~ 34% na eritromicin (16). Visoki nivoi rezistencije su zapaženi i u nekim drugim zemljama u okruženju.…”
Section: Diskusijaunclassified